The Likely World - Conroy-Goldman, Melanie (Book collections on Project MUSE., 2020)
"Twenty years of addiction to cloud, a drug which wipes the user's short-term memory, have left single mom Mellie with her mind in fragments. With the help of a tough-minded sponsor, and motivated by her own medically-challenged daughter, Mellie clings to a fragile sobriety. Then, on the evening of her twenty-ninth day sober, a stranger pulls into her driveway and her heart surges. However, when Mellie's pursuit of this man and the past they may share threatens her sponsor, Mellie will have to put her tiny family and her recovery at risk in hopes of saving the woman who saved her first." --